IGF-1R inhibition enhances radiosensitivity and delays double-strand break repair by both non-homologous end-joining and homologous recombination. - Chitnis, M; Lodhia, K; Aleksic, T; Gao, S; Protheroe, A; Macaulay, V (2014)
Inhibition of type 1 insulin-like growth factor receptor (IGF-1R) enhances tumor cell sensitivity to ionizing radiation. It is not clear how this effect is mediated, nor whether this approach can be applied effectively in the clinic. We previously showed that IGF-1R depletion delays repair of radiation-induced DNA double-strand breaks (DSBs), unlikely to be explained entirely by reduction in homologous recombination (HR) repair. The current study tested the hypothesis that IGF-1R inhibition induces a repair defect that involves non-homologous end joining (NHEJ). IGF-1R inhibitor AZ12253801 blocked cell survival and radiosensitized IGF-1R-overexpressing murine fibroblasts but not isogenic IGF-1R-null cells, supporting specificity for IGF-1R. IGF-1R inhibition enhanced radiosensitivity in DU145, PC3 and 22Rv1 prostate cancer cells, comparable to effects of Ataxia Telangiectasia Mutated inhibition. AZ12253801-treated DU145 cells showed delayed resolution of γH2AX foci, apparent within 1 h of irradiation and persisting for 24 h. In contrast, IGF-1R inhibition did not influence radiosensitivity or γH2AX focus resolution in LNCaP-LN3 cells, suggesting that radiosensitization tracks with the ability of IGF-1R to influence DSB repair. To differentiate effects on repair from growth and cell-survival responses, we tested AZ12253801 in DU145 cells at sub-SF50 concentrations that had no early (⩽48 h) effects on cell cycle distribution or apoptosis induction. Irradiated cultures contained abnormal mitoses, and after 5 days IGF-1R-inhibited cells showed enhanced radiation-induced polyploidy and nuclear fragmentation, consistent with the consequences of entry into mitosis with incompletely repaired DNA. AZ12253801 radiosensitized DNA-dependent protein kinase (DNA-PK)-proficient but not DNA-PK-deficient glioblastoma cells, and did not radiosensitize DNA-PK-inhibited DU145 cells, suggesting that in the context of DSB repair, IGF-1R functions in the same pathway as DNA-PK. Finally, IGF-1R inhibition attenuated repair by both NHEJ and HR in HEK293 reporter assays. These data indicate that IGF-1R influences DSB repair by both major DSB repair pathways, findings that may inform clinical application of this approach.